Ler ou não ler, eis a questão - Oliveira, Maria Clara Milanez de (Universidade do Vale do Rio dos Sinos, 2025)
This dissertation seeks to investigate reading practices in the initial years of a public school in the municipality of São Leopoldo (RS), based on a case study with a qualitative approach, from the perspective of post-critical research in education. Data production included narrative interviews with teachers and the person responsible for the school library, questionnaires with managers and observations in the empirical field. It describes theoretical perspectives on reading practices, education, school and contemporaneity and educational management. The data produced were categorized, described and analyzed based on the methodological bricolage movement. The analyses revealed that the predominant reading practices involve short, easily accessible texts, but some teaching initiatives demonstrate concern with the development of critical thinking, imagination and pleasure in reading. Educational management emerges as a key element in driving significant changes, ensuring access to books and encouraging literary and formative reading practices. The research also presents an intervention proposal, which consists of the creation of a Literary Workshop as continuing education for teachers in the municipal network, with the aim of strengthening teacher training and promoting more critical and literary reading practices. The study contributes to the debate on literary reading training in schools and reinforces the importance of teacher training so that reading can exercise its (trans)formative potential in education.
Keywords: Ateliê literário; Gestão educacional; Leitura nos anos iniciais; Leitura formativa; Leitura literária; Práticas de leitura; Literary studio; Educational management; Reading in the early years; Formative reading; Literary reading; Reading practices; ACCNPQ::Ciências Humanas::Educação